Inovasi Polri melalui Aplikasi Polri Super App Presisi pada Pelayanan Publik Surat Keterangan Catatan Kepolisian Online di Polres Pasaman - Rendhy Bin Hart Johanda; Khairul Khairul (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This research aims to find out the innovation of the Polri Super App application and explain the obstacles to its implementation in the online SKCK service at Pasaman Police Station. This research is descriptive qualitative research using case study research methods. Data were obtained using interview techniques, observation and documentation. The innovation of the Polri Super App application is analyzed using the four characteristics of innovation conveyed by Rogers and describes what obstacles are encountered in its implementation in online SKCK services at Pasaman Police Station. The results of the research on the characteristics of relative advantage innovation show that digitization through the Polri Super App application has made SKCK services at the Polres easier and more efficient, but SKCK collection is still carried out at the Pasaman Police SKCK service room. The compatibility innovation characteristic shows that the Polri Super App application has referred to the Polri Institutional Regulations and is in line with the habits of young people and is able to meet public demands for transparency in SKCK public services. The characteristics of innovation complexity show that people experience little complexity in using the Polri Super App application. The characteristics of innovation trialability show that the application of the Polri Super App application to SKCK services at Pasaman Police Station is applied without going through a trial stage first. The obstacles to the implementation of the Polri Super App application in online SKCK services at Pasaman District Police are limited internet access and geographical impacts in disseminating information and using the application. Technical problems with server disruptions in the application and the mindset of people who are reluctant to register for SKCK online using the Polri Super App application.